PENGARUH KOMITMEN PROFESIONAL, PENGALAMAN KERJA, DAN SANKSI PERPAJAKAN PADA PENGAMBILAN KEPUTUSAN ETIS KONSULTAN PAJAK DI PROVINSI BALI - I Gusti Putu Bayu Sanjaya Putra; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2021)
Profession in the accounting sector is a job that is often faced with ethical actions, especially work in the field of Tax Consultants. The purpose of this study was to see the effect of professional commitment, work experience, and tax sanctions on the ethical decision-making process of the Tax Consultant in Bali Province. The population in this study were all Tax Consultants in Bali Province, while the sample in this study used 223 people. Sampling with purposive sampling method. Data testing includes: validity, reliability, multicollinearity, heteroscedasticity, multiple regression analysis, hypothesis testing and coefficient of determination. The results of the study indicate that professional commitment, work experience, and tax sanctions simultaneously have a significant positive effect on ethical decision making for Tax Consultants in Bali Province.